Reorientasi Keagamaan Muhammadiyah dalam Konteks Globalisasi di Sulawesi Selatan - Muhammadong Muhammadong; Khaerunnisa Khaerunnisa; Nurmila Nurmila (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The reorientation introduced by Muhammadiyah aims to understand the purification doctrine that was developed. The entry of Islam into South Sulawesi cannot be separated from cultural influences that can affect the religious activities of the community. The strong understanding of syncretism that is implemented is a record for the organization to carry out restoration so that people can return to the Qur'an and the Sunnah of the Prophet so that the religion that is practiced is not mixed with superstition. In the context of globalization, the reorientation developed by Muhammadiyah must be free from the shadows of tradition because it has the potential to damage the foundation of faith because Islam is a straight religion, so it must be carried out in totality. Differentiation should not occur in social institutions because a society must be treated equally. In the field of education, Muhammadiyah takes a moderate path with the freedom of the curriculum which was developed due to the demands of globalization so that the orientation developed becomes a reorientation. However, lately, the purification movement has begun to be abandoned and tends to blend with the culture of the community in the religious field. Ritualism carried out by the community is always responded to even though it does not directly justify the law that has been caused but at least gives acknowledgment.